The impact of manipulating angle of projection and height of release on accuracy in the netball free throw / Siti Haslina Puteh - Puteh, Siti Haslina (2019)
Biomechanical research has exposed two characteristics of skilled shooters which are a high release point and a medium to high angle of projection. The aim of this experimental study was to determine if the angle of projection could be increased following a short training session and to explore the impact of manipulating angle of projection and height of release on accuracy. Fourteen subjects were randomly assigned to the control and experimental groups. All of them participated in individual pre-tests to determine height of release, accuracy and angle of projection. Free throws were videotaped and height of release ratio was determined by a formula, while accuracy of shots were calculated in percentage. Protractor application was used to determine angle of projection for each subject. Then, subjects in both groups were given individual post-test. Members in the experimental group had been provided with specific instructions in the post-tests. All of them needed to increase their angle of projection while members of the control group received no instruction. T-test revealed no significant differences (p > .5) between the two groups on neither height of release nor accuracy, but there was a significant difference (p=0.008) existed between the two groups on average angle of projection (AAOP). T-test on the post-test data revealed a significant difference between the groups on the three variables which are: height of release (p=0.019), accuracy (p=0.009) and average angle of projection (p=0.046). Shooters can increase their angle of projection after a training session. Manipulations of angles of projection and height of release ratio affects the accuracy. As both the height of release ratio and average angle of projection increase, the accuracy increase too.